Kajian Nilai Sosio Religius Pada Upacara Pattidāna Masyarakat Buddha - Tantra, Manggala Wiriya; Maharani, Septiana Dwiputri (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2024)
The death commemoration ceremony or pattidāna in Buddhism is a ceremony that has been carried out for generations by Buddhists, it is very interesting to research so that it can reveal its socio-religious values. The qualitative approach used in this research is phenomenology, considering that this research examines religious phenomena descriptively. There are two sources of data in this research, namely primary data sources obtained through interviews with the Buddhist community in Selorejo Village, Ngunut District, Tulungagung Regency. The results of this research reveal that the Pattidāna ceremony contains several socio religious values, including social values, religious moderation values and spiritual values. Social values are reflected in joint efforts in preparing food, drinks and various types of offerings voluntarily. The value of religious moderation can be seen in the neighbors and relatives who come to help with the pattidānaprayer process, not only Buddhists, but also from various religions including Islam, Christianity and Catholicism. Spiritual values appear during the preparation, implementation and after completion of the pattidāna ceremony, giving rise to a strong belief that the power of the good deeds that have been carried out provide happiness in itself which is actually part of spiritual maturity.